ДИНАМИКА ЭПИДЕМИОЛОГИЧЕСКИХ ПОКАЗАТЕЛЕЙ ПО ТУБЕРКУЛЕЗУ СЕМИПАЛАТИНСКОГО РЕГИОНА ЗА ПОСЛЕДНИЕ 37 ЛЕТ (1975-2011 Г.Г.) («Наука и здравоохранение», 2026)
For an avoidance of the further diffusion of an infection contamination and body height of a case rate by tuberculosisamong the population of Semipalatinsk region it is necessary to carry out (spend) the following measures:- To strengthen in region propaganda about tuberculosis with wide use of mass media:- By all subject to bunch of the population regularly to carry out (spend) against tuberculosis of engrafting.- To strengthen work on early revealing of tuberculosis, is especial among children, teenagers, youth, bunches of theraised (increased) risk of disease:- Regularly and in complete volume to carry out (spend) preventive and improving work in the locuses of tuberculosis:-Along with a specific chemotherapy to utilize nosotropic (pathogenetic) and surgical methods of treatment more widely.